2022
DOI: 10.1101/2022.06.08.495340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine tuning of CpG spatial distribution with DNA origami for improved therapeutic cancer vaccination

Abstract: Multivalent presentation of ligands often enhances receptor activation and downstream signaling. DNA origami offers precise nanoscale spacing of ligands, a potentially useful feature for therapeutic nanoparticles. Here we introduce a square-block DNA origami platform to explore the importance of spacing of CpG oligonucleotides, which engage Toll-like receptors and thereby act as danger signals for dendritic cells. Through in vitro cell-culture studies and in vivo tumor-treatment models, we demonstrate that squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…While nucleic acid nanodevices have been applied to various therapeutic areas, their immunostimulatory properties have been explored to a lesser degree. Such fundamental understanding of NANP immunological properties is important to inform the design of follow-on in vivo studies using CpG overhangs (e.g., Zeng et al, bioRxiv, and Oktay et al, bioRxiv), to further explore prophylactic and therapeutic potential of these nanomaterials. , By establishing a deeper understanding of the baseline immunostimulatory properties of unmodified wireframe NANPs and the relative impacts of various NANP design parameters on DNA nanoparticle-mediated tunable TLR9 activation, we can work toward enabling the design of DNA nanostructures with specific immunostimulatory profiles for targeted biological outcomes.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…While nucleic acid nanodevices have been applied to various therapeutic areas, their immunostimulatory properties have been explored to a lesser degree. Such fundamental understanding of NANP immunological properties is important to inform the design of follow-on in vivo studies using CpG overhangs (e.g., Zeng et al, bioRxiv, and Oktay et al, bioRxiv), to further explore prophylactic and therapeutic potential of these nanomaterials. , By establishing a deeper understanding of the baseline immunostimulatory properties of unmodified wireframe NANPs and the relative impacts of various NANP design parameters on DNA nanoparticle-mediated tunable TLR9 activation, we can work toward enabling the design of DNA nanostructures with specific immunostimulatory profiles for targeted biological outcomes.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…We first implemented origamiFISH in RAW264.7 macrophage cells, a widely utilized cell line within the DNA origami field with high DN uptake capacity (Kern et al, 2021; Liu et al, 2020; Maezawa et al, 2020; Zeng et al, 2022). Following our origamiFISH protocol, DNs appear as bright, distinct fluorescent puncta, or “spots”, within each cell ( Fig.…”
Section: Development and Validation Of Origamifish Imagingmentioning
confidence: 99%
“…Regarding the role of spacing between CpGs, it is demonstrated that when CpG is present in pairs, the DC stimulation is enhanced, and CD8 T cells are highly activated [ 103 ]. In the present study, in the native construct, no CpG dimer was present, while 04, 09, and 06 CpG dimers were present in constructs 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, in the native construct, no CpG dimer was present, while 04, 09, and 06 CpG dimers were present in constructs 1, 2, and 3. More CpGs in the sequence lead to increased IL10 and IL12 secretion [ 103 ]; thus highest IL10 and IL12 secretion will be there with construct 2.…”
Section: Resultsmentioning
confidence: 99%